2021
DOI: 10.29312/remexca.v12i3.2702
|View full text |Cite
|
Sign up to set email alerts
|

Patogenicidad de cepas de Ustilago maydis para la producción en condiciones controladas

Abstract: La amplia variabilidad patogénica en cepas de Ustilago maydis permite la evaluación en semillas de maíz hibridas y criollas para la producción de huitlacoche. Por lo anterior, el objetivo en este estudio fue evaluar la capacidad patogénica de cepas de U. maydis del estado de Aguascalientes, México durante el periodo 2014-2016 en maíces híbridos y criollos para la producción de huitlacoche en condiciones controladas con el método de inoculación artificial. Evaluando cuatro cepas de Aguascalientes y dos cepas te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Huitlacoche is a perishable edible fungus that, if grown traditionally, is only available usually for two months (July and August) [48]. However, the cultivation of this fungus, infecting the early stages of corn ears called "jilote" in Spanish, has already been achieved [58][59][60]. Furthermore, it has been reported that huitlacoche as a crop can be more profitable than maize itself, increasing the value of maize cultivars by 20 to 50 times their market price [61,62].…”
Section: Huitlacoche (Ustilago Maydis)mentioning
confidence: 99%
“…Huitlacoche is a perishable edible fungus that, if grown traditionally, is only available usually for two months (July and August) [48]. However, the cultivation of this fungus, infecting the early stages of corn ears called "jilote" in Spanish, has already been achieved [58][59][60]. Furthermore, it has been reported that huitlacoche as a crop can be more profitable than maize itself, increasing the value of maize cultivars by 20 to 50 times their market price [61,62].…”
Section: Huitlacoche (Ustilago Maydis)mentioning
confidence: 99%